Molecular dynamics simulations of water transport through carbon nanotubes - Wong, Zhi Hao. (2009)
There are many research papers which focus on the working mechanism which drives water through carbon nanotubes (CNTs). For instance, there are researches conducted on hydrogen bonds and diffusive coefficient has on the flow of water in CNTs. All of these researches are closely linked to the properties of water. With a better understanding on the properties of water, the flow of water through CNTs can then be closely studied by manipulating these properties.